Regulation of Store-Operated Ca(2+) Entry by Septins - Deb, Bipan K. (Front Cell Dev Biol, 2016)
The mechanism of store-operated Ca(2+) entry (SOCE) brings extracellular Ca(2+) into cells after depletion of intracellular Ca(2+) stores. Regulation of Ca(2+) homeostasis by SOCE helps control various intracellular signaling functions in both non-excitable and excitable cells. Whereas essential components of the SOCE pathway are well characterized, molecular mechanisms underlying regulation of this pathway need investigation. A class of proteins recently demonstrated as regulating SOCE is septins. These are filament-forming GTPases that assemble into higher order structures. One of their most studied cellular functions is as a molecular scaffold that creates diffusion barriers in membranes for a variety of cellular processes. Septins regulate SOCE in mammalian non-excitable cells and in Drosophila neurons. However, the molecular mechanism of SOCE-regulation by septins and the contribution of different subgroups of septins to SOCE-regulation remain to be understood. The regulation of SOCE is relevant in multiple cellular contexts as well as in diseases, such as the Severe Combined Immunodeficiency (SCID) syndrome and neurodegenerative syndromes like Alzheimer's, Spino-Cerebellar Ataxias and Parkinson's. Moreover, Drosophila neurons, where loss of SOCE leads to flight deficits, are a possible cellular template for understanding the molecular basis of neuronal deficits associated with loss of either the Inositol-1,4,5-trisphosphate receptor (IP(3)R1), a key activator of neuronal SOCE or the Endoplasmic reticulum resident Ca(2+) sensor STIM1 (Stromal Interaction Molecule) in mouse. This perspective summarizes our current understanding of septins as regulators of SOCE and discusses the implications for mammalian neuronal function.